(3eaghe GdLgGdI YfO GdeMOKjf (B: s (3OQGSI JWHjbjI ai cJH GdSff (B/ s - (3CMeO YHOGddg YjO GdeNjGds; (3YHOGdeLjO eMehO YHOGdeLjO (B: s ((3GdbGgQI (B: s (3CMeO YHOGddg YjO GdeNjGd (B: s, 2011)
(3CgJeJ gPg GdOQGSI HJhVjM eaghe GdLgGdI h MbjbJgG YfO GdeMOjKf h HjGf CdaGXgG h CSHGHgG h eYQaI hSGFd GQJaGYgG YfOge (B: (3gGOaI Edi QaO GdecJHI GdESdGejI HcJGH aj gPG de jSHb JfGhdg aj OQGSI MOjKjI TGedI (B: (3hGdGSgGe ai JejjR GdGMGOjK GdfHhjI h OQGSI deQhjGJ eLGgjd GNQL dge ai GdSff GdGQHYI h GbhGd GdfbGO ajge NOeI ddHGMKjf GdeJNUUjf ai Gdhbha Ydi gPg GdeQhjGJ h JMbjb Gdbhd ai QhGFgG Ohf YfGA h JYHs
(3GWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3cdjI OGQ GdYdhe (B- (3bSe GdTQjYI GdESdGejIs
(3UOQ GjVG cbQU eOeLs
Keywords: (3GGdeMOKjfs; (3GdLgGdI s; (3GdQhGI s